2017
DOI: 10.1042/bcj20170282
|View full text |Cite
|
Sign up to set email alerts
|

Reduced threshold for store overload-induced Ca2+ release is a common defect of RyR1 mutations associated with malignant hyperthermia and central core disease

Abstract: Mutations in the skeletal muscle ryanodine receptor (RyR1) cause malignant hyperthermia (MH) and central core disease (CCD), whereas mutations in the cardiac ryanodine receptor (RyR2) lead to catecholaminergic polymorphic ventricular tachycardia (CPVT). Most disease-associated RyR1 and RyR2 mutations are located in the N-terminal, central, and C-terminal regions of the corresponding ryanodine receptor (RyR) isoform. An increasing body of evidence demonstrates that CPVT-associated RyR2 mutations enhance the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Interestingly, the threshold for SOICR is reduced in many disease-linked mutations of both RyR1 and RyR2. Moreover, this functional defect contributes to explaining the overactive behavior of the corresponding mutant proteins, along with the human symptoms of central core disease (CCD), malignant hyperthermia (MH), and catecholaminergic polymorphic ventricular tachycardia (CPVT) [97,101]. The molecular bases underlying SOICR are not yet entirely clear.…”
Section: Cardiac Ec Couplingmentioning
confidence: 99%
“…Interestingly, the threshold for SOICR is reduced in many disease-linked mutations of both RyR1 and RyR2. Moreover, this functional defect contributes to explaining the overactive behavior of the corresponding mutant proteins, along with the human symptoms of central core disease (CCD), malignant hyperthermia (MH), and catecholaminergic polymorphic ventricular tachycardia (CPVT) [97,101]. The molecular bases underlying SOICR are not yet entirely clear.…”
Section: Cardiac Ec Couplingmentioning
confidence: 99%
“…wave was investigated. It was previously found that the activation of MHS causative RyR variant by halothane was dependent on the luminal SR Ca 2+ reaching above an 'storeoverload induced Ca 2+ release (SOICR) threshold' (Jiang et al, 2008;Chen et al, 2017).…”
Section: Propagation Of Ca 2+ Waves Is Dependent On the Luminal Sr Ca 2+mentioning
confidence: 99%
“…This suggests that even in conditions which favours CICR (by reducing competition by Mg 2+ ) the threshold required for Ca 2+ to activate the RyR1 cannot be met solely by a cytoplasmic propagating mechanism. It is also important to note that MHS RyR1 variants do not have an increased sensitivity to cytosolic Ca 2+ activation (Murayama et al, 2007;Chen et al, 2014;Chen et al, 2017).…”
Section: 'Classic' Cicr Does Not Contribute To Ryr1 Activation Duringmentioning
confidence: 99%
See 2 more Smart Citations